Clinical profile and prognostic factors of alcoholic cardiomyopathy in tribal and non-tribal population. Issue 2 (24th November 2020) - Dungdung, Ajit; Kumar, Abhinav; Guria, Rishi Tuhin; Preetam, Mukul; Tara, Ruth K; Kumar, Bindey; Saba, Mohammad Kamal
Abstract : Objective: Alcoholic cardiomyopathy (ACM) is a leading cause of non-ischaemic dilated cardiomyopathy (DCM) in tribal and non-tribal population. However, no study has been done depicting the correlation between clinical profile and prognosis of ACM in tribal and non-tribal population. This study also defines the long-term outcome and prognostic markers of ACM. Methods: We studied 290 patients with ACM who were evaluated in our institute between January 2013 and December 2016. The primary endpoint of the study was all-cause mortality. Statistical analysis was done by using Kaplan-Meier survival curves for the assessment of all-cause mortality and Cox regression for the assessment of risk factors. Results: After a median follow-up period of 3.75 years (IQR: 3–4 years), 50 patients with ACM (37.3%) died among tribal population while 14 patients (9%) died among non-tribal population. Independent predictors of all-cause mortality in ACM identified by Cox regression were left ventricular ejection fraction (LVEF) (HR: 0.883; 95% CI 0.783 to 0.996; p=0.043), QRS duration (HR: 1.010; 95% CI 1.007 to 1.017; p=0.005) and Child-Turcotte-Pugh (CTP) Scoring (HR: 12.332; 95% CI 6.999 to 21.728; p<0.001) at admission. The Kaplan-Meier survival probability estimate was 95.1% at 1 year and all-cause mortality was found to be higher in patients with QRS>120 ms, LVEF ≤35%, CTP Grade B/C than patients with QRS≤120 ms, LVEF >35% and CTP Score A, respectively (log-rank χ²=55.088, p<0.001; log-rank χ²=32.953, p<0.001; log-rank χ²=139.764, p<0.001, respectively). Conclusion: Our study indicated increased morbidity and mortality in tribal population. LVEF, QRS duration and CTP Scoring at the time of presentation were found to be the independent prognostic markers of patients with ACM.